Suomalainen koulutus kansainvälisillä markkinoilla – valtionhallinto koulutusviennin mahdollistajana ja koulutuksen maineen vaalijana - Heli Tirri; Heikki Silvennoinen (Hallinnon tutkimuksen seura, 2022)
In Finland education is a public service, mainly free of charge. In this context it is reasonable to ask how do educational values and business values fit together. How do top public administrators see education as a market commodity in the international business field? What ethical questions and solutions have emerged in the field of education export, and why they are important to the actors? The study is based on interviews with four state administrators working with education export and representing national interest. The state administrators have encountered a number of ethical problems in advancing education export. However, they have come up with several solutions to ethical dilemmas.